Genetic Incorporation of a Reactive Isothiocyanate Group into Proteins. (15th July 2016) - Xuan, Weimin; Li, Jack; Luo, Xiaozhou; Schultz, Peter G.
Abstract: Methods for the site‐specific modification of proteins are useful for introducing biological probes into proteins and engineering proteins with novel activities. Herein, we genetically encode a novel noncanonical amino acid (ncAA) that contains an aryl isothiocyanate group which can form stable thiourea crosslinks with amines under mild conditions. We show that this ncAA (pNCSF) allows the selective conjugation of proteins to amine‐containing molecular probes through formation of a thiourea bridge. pNCSF was also used to replace a native salt bridge in myoglobin with an intramolecular crosslink to a proximal Lys residue, leading to increased thermal stability. Finally, we show that pNCSF can form stable intermolecular crosslinks between two interacting proteins.